2021
DOI: 10.1108/dlp-10-2020-0106
|View full text |Cite
|
Sign up to set email alerts
|

Research data services from the perspective of academic librarians

Abstract: Purpose This study aims to investigate the perceptions of academic librarians regarding research data services (RDS) in academic library environments. This study also examines a range of challenges in RDS from the perspectives of academic librarians. Design/methodology/approach A nationwide online survey was administered to academic librarians engaged in data services at research universities around the USA. The collected survey responses were analyzed quantitatively using descriptive statistics, hierarchica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Approximately 75% of responding libraries provide an institutional research repository. Previous studies (Thompson et al, 2015;Reed, 2015) as well as the recent study by Joo and Schmidt (2021) have confirmed the importance of an institutional repository service among researchers, as it enables libraries to provide them with access to the intellectual work of the parent institution. In addition, such a service increases external, i.e.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Approximately 75% of responding libraries provide an institutional research repository. Previous studies (Thompson et al, 2015;Reed, 2015) as well as the recent study by Joo and Schmidt (2021) have confirmed the importance of an institutional repository service among researchers, as it enables libraries to provide them with access to the intellectual work of the parent institution. In addition, such a service increases external, i.e.…”
Section: Discussionmentioning
confidence: 82%
“…That said, it should be noted that newer studies on RSS, and particularly RDS, have highlighted the challenges which libraries face in allocating research support staff. Cox et al (2019), Tenopir et al (2019a) and Joo and Schmidt (2021), for example, have reported on insufficient library staff, limited awareness among library staff, lack of training and insufficient time as major factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that the most perceived critical data services were "assistance with data archiving", "assistance with data preservation", or "assistance with data documentation", among others. They also found that the primary skills useful for research data service were "developing and teaching instructional content related to data services", "data management planning", and "data ethics" (Joo & Schmidt, 2020).…”
Section: Training Self-training and Other Trainingmentioning
confidence: 99%